A comparison of Denagard, Denagard/CTC and Pulmotil on nursery pig growth performance and economic return - K M Sotak; M Hammer; J Y Jacela; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 880 weanling pigs (initially 15.6 lb and 16 to 20 d of age) were used in a 41-d experiment to compare the effects of different antibiotic regimens on growth performance and economic return in the nursery phase. Pigs were alloted to 1 of 5 treatment groups based on weight within gender. The antibiotic regimens included: (1) control diets containing no antibiotic throughout the trial, (2) a combination of Denagard (Novartis Animal Health, Greensboro, NC) at 35g/ton and chlortetracycline at 400g/ton (Denagard/CTC) for the entire 41-d trial, (3) a Pulmotil (Elanco, Greenfield, IN) regimen of 363g/ton from d 0 to 10 followed by 181g/d from d 10 to 41, (4) Denagard 200 from d 0 to 10 followed by Denagard/CTC from d 10 to 41, and (5) Denagard/CTC from d 0 to 10, Denagard 200 from d 10 to 20, and Denagard/ CTC from d 20 to 41. From d 0 to 10, ADG, ADFI, and F/G were similar (P>0.40) between the pigs fed nonmedicated diets and the mean of the groups fed diets containing antibiotics. However, from d 10 to 20, 20 to 41, and for the overall trial, pigs fed diets containing antibiotics had greater (P<0.05) ADG and improved (P<0.04) F/G than pigs fed the control diet without antibiotics. Pigs fed diets containing Denagard/ CTC had greater (P<0.02) ADG and ADFI than pigs fed Pulmotil for d 0 to 10, 20 to 41, and the overall trial. No differences were found (P>0.18) between pigs fed Denagard/CTC and Denagard 200 during any phase. Final pig weights were greater for pigs fed diets containing antibiotics compared with the control (P<0.01) and for pigs fed Denagard/CTC compared with pigs fed Pulmotil (P<0.05). Adding antibiotics to the diets increased (P<0.01) feed cost per pig; however, income over feed cost (IOFC) also increased for pigs fed Denagard/CTC compared with the control (P<0.01) and compared with pigs fed Pulmotil (P<0.01). These results demonstrate that adding antibiotics to the nursery diet improved pig performance and economic return.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Antibiotic; Denagard; Pulmotil